Elective affinities or random choice within the seagrass holobiont? The case of the native Posidonia oceanica (L.) Delile and the exotic Halophila stipulacea (Forssk.) Asch. from the same site (Limassol, Cyprus) - Conte, Chiara; Rotini, Alice; Winters, Gidon; Vasquez Christodoulou, Marlen; Piazza, Giulia; Kletou, Demetris; Migliore, Luciana (My University, 2021)
Seagrasses and associated microbial communities constitute a functional unit (holobiont) which responds as a whole to environmental changes. However, it is still unclear how the microbial colonizers are selected. In this study we compared the epiphytic microbial communities associated with Posidonia oceanica and Halophila stipulacea, Mediterranean native and exotic seagrass species, respectively, growing side by side in monospecific patches within the port of Limassol (Cyprus, Eastern Mediterranean Sea). To evaluate whether the environment rather than the host species and/or its physiological condition play a role in shaping the seagrass epiphytic microbial community, the environmental microbial communities (seawater and sediment) and seagrass associated ones were determined by using 16S rRNA gene amplicon sequencing. Plant ecological status was evaluated by morphological (biometry), structural (density) and biochemical (pigment/phenol content) descriptors. In both species, leaf associated microbial communities are clearly similar to seawater microbes; conversely, microbes associated with H. stipulacea roots/rhizomes differ from the microbial communities in surrounding sediment. In both seagrasses, Pseudomonadaceae was the most abundant family on leaves, but each species harboured unique microbial families. To our best knowledge, this is the first study on these two neighbouring seagrass species, coupling plant ecological status with associated microbial communities. Results demonstrated that each seagrass responded differently to the same environmental conditions and selected different epiphytic microbial communities, supporting their putative use as ecological indicators.
Keywords: Ecological descriptors; Exotic species; Halophila stipulacea; Posidonia oceanica; Seagrass ecology; Seagrass holobiont